Implementation of the Suroboyo Bus Program at the Surabaya City Transportation Department - Moch. Bintang Kholili; Suci Megawati; Indah Prabawati; M. Noer Falaq Al Amin (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This research is motivated by the initiative of the Surabaya City Government in providing safe, comfortable, and affordable public transportation services through the Suroboyo Bus Program to reduce the level of congestion. Although strategic, the implementation of this policy still faces major obstacles in the form of budget limitations that have a direct impact on fleet maintenance, the provision of bus stop facilities, and the development of service routes. In addition, the problem of long waiting times and low public literacy of operational mechanisms also hinder the achievement of targets. This study aims to describe the implementation of the Suroboyo Bus Program at the Surabaya City Transportation Agency using the George C. Edwards III model which includes communication variables, resources, disposition, and bureaucratic structure. The approach used is qualitative descriptive with data collection techniques through interviews, observations, and documentation studies. Data analysis is carried out systematically through the stages of reduction, presentation, and drawing conclusions. The results of the study show that the implementation of the program has not been optimal. In the aspect of communication, socialization has not reached all levels of society equally. From the dimension of resources, budget limitations are the dominant inhibiting factor for the quality of facilities and infrastructure. However, the implementing disposition shows a strong commitment and the bureaucratic structure has been supported by adequate Standard Operating Procedures (SOPs). The research concludes that the success of the program requires strengthening fiscal support, improving the quality of public facilities, and intensifying socialization massively to optimize the implementation of public transportation in the city of Surabaya in order to achieve the policy goals that have been set.